Scalable reduction collectives with data partitioning-based multi-leader design - Bayatpour, Mohammadreza; Chakraborty, Sourav; Subramoni, Hari; Lu, Xiaoyi; Panda, Dhabaleswar K. (DK) (International Conference for High Performance Computing, Networking, Storage and Analysis (Online), 2017)
Existing designs for MPI_Allreduce do not take advantage of the vast parallelism available in modern multi-/many-core processors like Intel Xeon/Xeon Phis or the increases in communication throughput and recent advances in high-end features seen with modern interconnects like InfiniBand and Omni-Path. In this paper, we propose a high-performance and scalable Data Partitioning-based Multi-Leader (DPML) solution for MPI_Allreduce that can take advantage of the parallelism offered by multi-/many-core architectures in conjunction with the high throughput and high-end features offered by InfiniBand and Omni-Path to significantly enhance the performance of MPI_Allreduce on modern HPC systems. We also model DPML-based designs to analyze the communication costs theoretically. Microbenchmark level evaluations show that the proposed DPML-based designs are able to deliver up to 3.5 times performance improvement for MPI_Allreduce for multiple HPC systems at scale. At the application-level, up to 35% and 60% improvement is seen in communication for HPCG and miniAMR respectively.